Book Review: Chinese Acupuncture [l'Acuponcture Chinoise: La Tradition chinoise classifiée, precisée]. (Paris: Maloine, 1972). By George Soulié de Morant. Translated by Lawrence Grinnell, Claudy Jeanmougin and Maurice Leveque. Edited by Paul Zmiewski. Brookline, Mass.: Paradigm Publications, 1994. xxxii, 896 pp. $125.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800040171/resource/name/firstPage-S0021911800040171a.jpg
Keywords: book.review; dept.his

Book Review: Sexual Attraction and Childhood Association: A Chinese Brief for Edward Westermarck. By Arthur P. Wolf. Stanford, Calif.: Stanford University Press, 1995. xxiii, 561 pp. $65.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002191180002934X/resource/name/firstPage-S002191180002934Xa.jpg
Keywords: book.review; dept.his

Book Review: Essays Into Vietnamese Pasts. Edited by K. W. Taylor and John K. Whitmore. Ithaca, N.Y.: Southeast Asia Program, Cornell University Press, 1995. 288 pp. $20.00 (paper). - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800029971/resource/name/firstPage-S0021911800029971a.jpg
Keywords: book.review; dept.his

To Cope with a Bad Global Image: Human Rights in the People's Republic of China,1993-1994. - Lee, Ta-ling (Fall;History., 1996)
Keywords: dept.his; faculty_collection; sabbatical_report

History of the American Women's Hospitals in the early 20th century. - Quiroga, Virginia Anne Metaxas (1996)
Keywords: dept.his; faculty_collection; sabbatical_report

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Délicieux, 3 September-8 December 1319 - Friedlander, Alan (Transactions of the American Philosophical Society ; v. 86, pt. 1, 1996)
Keywords: Bernard, Délicieux, frère, approximately 1260-approximately 1320; Trials, litigation, etc; dept.his; faculty_collection

Book Review: Michael r. dutton, policing and punishment in china , london and new york: cambridge university press, 1992. pp. xii, 391. 74.95 (ISBN 0-521-40097-X). - Lee, Taling; Dutton, Michael R (Law and History Review, 1996)
Keywords: book.review; dept.his